Factors Related to the Incedent of Cervical Cancer In Obstetrics & Gynecology Department at Ulin Hospital Banjarmasin - Sundari Sundari; Adriana Palimbo; Ella Ella (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Objective: Identify and analyze factors of cervical cancer related to the age of first married, parity, the use contraception in Obstetrics Gynecology at Ulin Hospital Banjarmasin.Methods: This research used analytical survey with the case-control approach. Sampling technique in the research was total sampling with 90 samples in Obstetrics Gynecology at Ulin Hospital Banjarmasin. Data collection was by using a checklist with data processing chi-square test.Results:Chi-square test shows that there was a significant relationship between the age of married first 20 years p = 0.023 with OR 2.0 more risk than age ≥20 years, parity 3 p = 0.033 with OR 1.92 more risk than parity 1- 3, and prolonged use of contraceptive ≥4 years p = 0.025 with OR 0.50 was more risk than the duration of contraceptive use 4 yearsConclusion: There was a very significant relationship between the age of first marriage, parity and also the use of contraception with the incidence of cervical cancer.Keywords: age of first married, Cervical cancer, contraceptive use, parity.